COVID-19 Vaccine Hesitancy Among Health Care Workers in Four Health Care Systems in Atlanta. (3rd May 2022) - Kandiah, Sheetal; Iheaku, Onyinye; Farrque, Mirza; Hanna, Jasmah; Johnson, Kalisha Bonds; Wiley, Zanthia; Franks, Nicole M; Carroll, Kelley; Shin, Sangmin Ryan; Sims, Kanika Michele; Kulshreshtha, Ambar; ,
Abstract: Coronavirus disease 2019 (COVID-19) vaccine hesitancy among health care workers (HCWs) undermines community vaccine confidence. Predictors and reasons for HCW hesitancy in the Atlanta region were evaluated using a survey between May and June 2021. Vaccine hesitancy was highest in younger and less educated HCWs. Interventions to address vaccine hesitancy in HCWs are necessary.